Uji Kadar Formalin pada Tahu yang di Jual di Kabupaten Karawang dengan Metode Spektrofotometer Visible - Rifdah Fadhilah; Vesara Ardhe Gatera; Lely Sulfiani Saula; Sakiran Sakiran (Peneliti.net, 2022)
Abstract: Foods such as tofu basically do not last long to be stored, because the ingredients contain high water content. The relatively short storage of food is certainly detrimental to producers or the food industry. This study aims to detect formaldehyde in tofu and organoleptic tests on tofu in several traditional markets in Karawang Regency. The method used in this formalin analysis is the Nash reagent method. The results showed that from 5 total samples of sampling results in several traditional markets in Karawang Regency, 1 sample of them was positive for formalin with a concentration of 38.16 g/g. The results of the organoleptic test showed that the samples containing formalin had a chewy texture and had good physical condition on the 3rd day under refrigeration or room temperature storage conditions. Meanwhile, if the tofu is not formalized, it will be destroyed and only able to last one/two days. Based on the results of the study, it can be concluded that from the five tofu samples, the T1 sample was positive for formalin with a level of 38.16 g/g. Tofu containing formalin has thickening properties and has a shelf life of more than 3 days at refrigerator or room temperature. Keyword: Tofu, Nash Reagent, Formalin